MANAJEMEN DALAM MENGEMBANGKAN PELAYANAN MUSIK GEREJAWI - utomo, yunatan krisno (P3M STT Kristus Alfa Omega, 2023)
AbstractProfessionally implemented music management can create quality growth. This study aims to analyze the obstacles that exist in the ecclesiastical sphere related to the management of church music services. The author uses qualitative methods to be able to answer these questions comprehensively. The results of this study found that the resources owned by the church are very diverse, and this can be a strength as well as a weakness. So music management that is carried out professionally, planned, organized and well monitored can produce the expected growth in music quality.